Optimizing food-assistance programs: Nutrition-sensitive food assistance lowers anemia prevalence in Burundi - Leroy, Jef L.; Olney, Deanna K.; Ruel, Marie T.; Brown, Tracy (International Food Policy Research Institute, 2018)
Evidence shows that food-assisted maternal and child health and nutrition (FA-MCHN) programs that target mothers and children during the first 1,000 days of life (from pregnancy to a child’s second birthday) succeed in achieving nutrition improvements. What are the effects of such programs on anemia (i.e., low hemoglobin levels), specifically, in mothers and children? Women and children in the first 1,000 days are at particular risk of anemia. Anemia during pregnancy increases the chance of maternal mortality and has been associated with increased perinatal mortality, low birth weight, and, when caused by iron deficiency, delays in child development. Developmental delays, in turn, can have lifelong consequences, as they hinder cognitive development, school performance, employment, and accumulation of wealth. Certain components of FA-MCHN programs may help to reduce anemia, including the distribution of micronutrientfortified commodities, behavior change communication (BCC) strategies around optimal child feeding and hygiene and health practices (for example, promoting the use of bednets to prevent malaria, an important cause of anemia), and the strengthening of health services.